Prevalence and risk factors for asymptomatic intestinal microsporidiosis among aboriginal school children in Pahang, Malaysia - Anuar, T.S.; Bakar, N.H.A.; Al-Mekhlafi, Hesham Mahyoub; Moktar, N.; Osman, E. (SEAMEO Regional Tropical Medicine and Public Health Network, 2016)
The epidemiology and environmental factors affecting transmission of human microsporidiosis are poorly understood. We conducted the present study to determine the prevalence and risk factors associated with asymptomatic intestinal microsporidiosis among aboriginal school children in the Kuala Krau District, Pahang State, Malaysia. We collected stool samples from 255 school children and examined the samples using Gram-chromotrope Kinyoun stain. We also collected demographic, socioeconomic, environmental and personal hygiene information using a pre-tested questionnaire. Sixty-nine of the children was positive for microsporidia: 72.5% and 27.5% were low (1+) and moderate (2+) excretions of microsporidia spores, respectively. Univariate and multivariate analyses showed being aged ≥10 years (p = 0.026), using an unsafe water supply as a source for drinking water (p = 0.044) and having close contact with domestic animals (p = 0.031) were all significantly associated with microsporidial infection among study subjects. Our findings suggest asymptomatic intestinal microsporidiosis is common in the study population, more than previously reported. In the study population, control measures need to be implemented, such as good personal hygiene, proper sanitation and safe drinking water supply.